Penguatan Strategi Pemasaran Sebagai Upaya Pertahanan Usaha Mikro Milik Warga: Indonesia - Shifa Rahmani; Maman Rosama KM (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2021)
The impact of the Covid-19 pandemic has affected all sectors without exception the economic sector, all existing conditions are forced to change and must adjust if they do not do so they will be left behind. This is what is experienced by micro entrepreneurs, their opinion continues to decrease drastically due to this phenomenon. If it continues without changes and defense efforts, there will be no hope for its business to survive let alone develop. Not to mention matters relating to fulfilling their daily necessities, which they only rely on from the net income of their business. Changes need to be made, one of which is through coaching community owners of micro businesses, by providing material content that focuses on implementing effective marketing strategies adapted to current conditions. Even though they have received capital assistance from the Government, this must still be done in order to increase the capacity of micro business owners so that they can independently maintain their businesses and even develop them, so that their daily needs can be met which in turn can help create welfare for micro business owners.